THE IMPLEMENTATION OF INCLUSIVE EDUCATION AS A STRATEGY FOR TRANSFORMING THE LEARNING SYSTEM TO ACHIEVE EQUALITY AND FAIRNESS FOR ALL STUDENTS IN INDONESIA: A LITERATURE REVIEW BASED ON THEORETICAL ANALYSIS AND EMPIRICAL PRACTICE - Abdul Wahab Syakhrani (Adisam Publisher, 2025)
This study examines the implementation of inclusive education as a strategy for transforming the learning system in Indonesia to achieve equality and fairness for all students. Using a literature review approach based on theoretical analysis and empirical practice, this study integrates various theories of critical education, social justice, and universal design for learning with empirical findings from various regions in Indonesia. The results of the study show that inclusive education is capable of breaking down discriminatory barriers in the learning system and strengthening the participation and empowerment of learners with diverse needs. However, the success of its implementation is influenced by the readiness of teachers, infrastructure, socio-cultural support, and supportive cross-sectoral policies. This study recommends strengthening educator capacity, improving access to technology, and holistic policy coordination as key factors in expanding and strengthening inclusive education in Indonesia. Thus, inclusive education has proven to be an effective strategy for transforming the learning system to be fair and inclusive in the country.